1999
DOI: 10.1017/s1357729800050918
|View full text |Cite
|
Sign up to set email alerts
|

Variance components due to direct and maternal effects and estimation of breeding values for 12-week weight of Welsh Mountain lambs

Abstract: The purpose of this study was to examine the importa~zce of the genetic arld maternal enviroizmental factors ilifluencing the 12-week weight ( 1 2 W W ) of Welsh Mountain lambs arzd to estimate genetic parameters for this trait. Records of 8880 Welsh Mourztain lambs borrl betweeiz 1979 and 1995 were analysed. The records werefrom the rlucleus flock of the C A M D A cooperative breeding group. In this flock selection of replacements had been based on a multi-trait index incorporating lamb growth and materrzal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
2
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 19 publications
(10 reference statements)
6
12
2
1
Order By: Relevance
“…Models 3 and 4, which included the additive maternal effect but not the maternal environmental effect, yielded smaller estimates of σ a 2 and h 2 d than did Models 1 and 2. The same result was found in previous reports which compared models for various goat and sheep breeds (Saatci et al, 1999;Ligda et al, 2000;Szwaczkowski et al, 2006;Roy et al, 2008). Meyer (1992) showed that models not accounting for maternal genetic effects could result in substantially higher estimates of additive direct genetic variance and, therefore, higher estimates of h 2 d .…”
Section: Resultssupporting
confidence: 87%
“…Models 3 and 4, which included the additive maternal effect but not the maternal environmental effect, yielded smaller estimates of σ a 2 and h 2 d than did Models 1 and 2. The same result was found in previous reports which compared models for various goat and sheep breeds (Saatci et al, 1999;Ligda et al, 2000;Szwaczkowski et al, 2006;Roy et al, 2008). Meyer (1992) showed that models not accounting for maternal genetic effects could result in substantially higher estimates of additive direct genetic variance and, therefore, higher estimates of h 2 d .…”
Section: Resultssupporting
confidence: 87%
“…These reductions in, especially, σ 2 e were significant and amounts to 41% and 25% respectively for birth and weaning weight (not presented), indicating that some of the temporary environmental variance has been attributed to σ 2 e and some to σ 2 pe when c 2 te was not fitted. Similar general patterns were reported by Maniatis & Pollot (2002) for 8-week weight in Suffolk sheep and Saatci et al, (1999) for 12-week weight in Welsh mountain sheep. According to Al-Shorepy & Notter (1998) these effects include not only common environmental effects unique to the litter but also non-additive genetic effects expressed in full-sibs and genotype x year interaction effects expressed in the dam.…”
Section: Resultssupporting
confidence: 85%
“…Maternal heritability decreased with age, which confirms the proposal by Robison (1981) that maternal effects in mammals are substantial in young animals but diminish with age. Maternal heritability estimates of birth and weaning weights in this study were higher than values reported by Maria et al (1993), Snyman et al (1995), Yazdi et al (1997), Saatci et al (1999), Ligda et al (2000), Neser et al (2001), and Ekiz et al (2004) for several sheep breeds. The high estimates of maternal heritability for 9-month and yearling weights were unexpected because at these ages individuals do not depend on their mother and their weights should reflect only the direct effect of the genes on growth except for carry over maternal effects from before weaning.…”
Section: Resultscontrasting
confidence: 81%